Natural Rubber And Natural Rubber Grafted Chitosan Films For Removal Of Dyes - Hasanuddin, Nurul Hasliza (2019)
In this study, adsorption experiments of methylene blue (MB) onto the surface of natural rubber (NR) were accomplished under optimized conditions of initial dye concentration, pH and temperature. The adsorption process of MB onto NR in the concentrations range from 3.2 mg L’1 — 16.0 mg L"1 were found to follow linearized pseudo 2nd order: Type 1. The adsorption isotherm of NR onto MB obeyed the Langmuir isotherm with an agreement of R2= 0.9750. The calculated values of AH, AS, AG and Ea were found to be -21732.58 J mol’1, +14.24 J K‘* mol and - 26047.30 J mol'1 and +23.71 kJ mol'1 respectively. This adsorption study was shown to be spontaneous and exothermic in nature. However, NR took days to adsorb MB and failed to adsorb methyl orange (MO). Thus NR grafted chitosan (NR-g-Chi) with varied ratios of 80:20, 75:25 and 70:30 were implemented to improve the adsorption performance. The unpurified and purified NR-g-Chi was characterized using FTIR, TGA and DSC. Both NR and NR-g-Chi were studied for their PZC and swelling behavior. The performance adsorption of MB using NR-g-Chi showed better results than NR adsorption itself with shorter time taken.